Teaching Innovation Proposal: The Inclusion of Transversal Competences in Official University Studies of Master’s degrees and the Strengthening of Democratic Values - Ordóñez Olmedo, Eva (IJERI: International Journal of Educational Research and Innovation, 2017)
The present study is the result of a teaching innovation proposal carried out at Pablo de Olavide University (UPO), which was born from the work team of the Graduate Center (CEDEP), an organ in charge of organizing, managing and supervising every postgraduate program offered by this University. The objective of this qualitative exploratory research is to analyze the current reality of the official university studies of Masters’ degrees in the field of competences. Through the data interpretation technique of the documentary content analysis of 135 reports issued by the Direction of Evaluation and Accreditation of the Andalusian Knowledge Agency (DEVA), a need to implement transversal competences at the master level, common to all degrees offered, linked to some training complements to ensure their acquisition, has been identified. That is why, through innovative teaching methods, six transversal competences in masters’ degrees have been included, strengthening democratic values.